Survey of the implementation of the recommendations in the Health Service Circular 2002/009 'Better Blood Transfusion'. - Murphy, M; Howell, C (2005)
This report describes the results of questionnaire surveys in 2003 and 2004 on the implementation of the recommendations of the Health Service Circular (HSC) 'Better Blood Transfusion' 2002/009 for improving transfusion practice. These followed a similar survey in 2001 to determine the progress with the implementation of recommendations in the previous Health Service Circular (HSC) 'Better Blood Transfusion' 1998/224. There was a disappointing response rate (47%) to the 2003 survey and evidence for incomplete compliance with the action plan. It was repeated in April 2004 with a systematic approach to encouraging returns, and the response rate was 95%. The results indicate progress in the implementation of Better Blood Transfusion between 2001 and 2004 in relation to increases in the proportion of hospitals with Hospital Transfusion Committees, the training of some staff groups, the number of hospitals with transfusion practitioners, the development of protocols for the use of blood and audit activity. However, the results also indicate the need for further progress in the training of some staff groups, particularly nurses and doctors, the development of Hospital Transfusion Teams, the development of protocols for the appropriate use of blood, the provision of information to patients and the use of peri-operative cell salvage. This information should be used to plan further local, regional and national initiatives to implement the Better Blood Transfusion action plan and improve transfusion practice.